PENGARUH SALINITAS BERBEDA TERHADAP PERTUMBUHAN DAN KELULUSHIDUPAN BENIH IKAN NILA MERAH (Oreochromis sp.) - Imansyah Dahril; Usman M Tang; Iskandar Putra (Berkala Perikanan Terubuk, 2017)
This research was conducted on March 6th until April 7th, 2017 at Coastal Fish Hatchery (CFH) of Bengkalis which located on Mariaman Street, Teluk Papal Village, Bantan Subdistrict, Bengkalis District, Riau Province. The purpose of this experiment was to determine the best salinity toward growth performance and survival rate of red tilapia fingerling (Oreochromis sp.). The method used was experimental method with Completely Randomized Design (CRD) model with 1 factor consisting of 5 treatment levels and 4 times replications (20 experimental units). The treatments used in this research were: 1) 11 ppt; 2) 14 ppt; 3) 17 ppt; 4) 20 ppt; And 5) 23 ppt of salinity. During 32 days maintenance was obtained the best treatment was at 17 ppt of salinity with absolute weight growth was 2,26 g, absolute length growth was 2,68 cm, the specific growth rate was 7.01% and the highest survival rate was at 14 ppt and 17 ppt as much as 98,75 %. Water quality parameters during the experiment were temperature (29-30oC), DO (5.20-5.65 mg/L), pH (7.5-8.0) and TAN (0.25-0.50 mg/L )